Analysis of service properties of cylindrically ground surfaces, using standard ISO 25178-2:2012 surface texture parameters (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
At present surface roughness is one of the main indications of component quality. During the operation mainly the outer layer of the component is exposed to external action, and depending on the roughness structure conclusions can be drawn about the service properties of the surface. Because cylindrical grinding today is rather widely used and precise method of treatment of bodies of revolution in the field of mechanical engineering the given paper pays attention to the surfaces treated on cylindrical grinding machines, and more exactly to their roughness, determining the possible use of the given surfaces. For the analyses of the roughness parameters the ISO standard ISO 25178-2:2012”Geometrical product specifications (GPS) — Surface texture: Areal — Part 2: Terms, definitions and surface texture parameters” was used, in which there were determined the texture parameters of the surface. Contrary to other standards, such as ISO 4287, ISO 13565 the new standard allowed to assess real surface properties, since in the given case the surface is being viewed in three-dimension space. During the research three cylindrically ground samples treated at different cutting conditions were chosen. By the help of modern measuring equipment Taylor Hobson Talysurf Intra 50 the topography of the given samples was taken in order to obtain and compare the roughness parameters and for the purpose of setting relation between the cutting regime and roughness parameters, and determining mathematical model of cylindrically ground samples. As a result of research it was stated that the given type of surfaces is characterized by irregular roughness, that is location of micro-peaks regarding their height and shape are irregular and also the correlation function of cylindrically ground surfaces is rapidly diminishing, but the density distribution of ordinates is close to normal. Based on the above feature of surface roughness such service properties as wear resistance, retention of lubricants and coatings (adhesion) and provision of required contact area were determined.